Frameless Stereotactic Brain Biopsies: Comparison of Minimally Invasive Robot-Guided and Manual Arm-Based Technique. Issue 3 (15th May 2020) - Minchev, Georgi; Kronreif, Gernot; Ptacek, Wolfgang; Kettenbach, Joachim; Micko, Alexander; Wurzer, Ayguel; Maschke, Svenja; Wolfsberger, Stefan
Abstract: BACKGROUND: Most brain biopsies are still performed with the aid of a navigation-guided mechanical arm. Due to the manual trajectory alignment without rigid skull contact, frameless aiming devices are prone to considerably lower accuracy. OBJECTIVE: To compare a novel minimally invasive robot-guided biopsy technique with rigid skull fixation to a standard frameless manual arm biopsy procedure. METHODS: Accuracy, procedural duration, diagnostic yield, complication rate, and cosmetic result were retrospectively assessed in 40 consecutive cases of frameless stereotactic biopsies and compared between a minimally invasive robotic technique using the iSYS1 guidance device (iSYS Medizintechnik GmbH) (robot-guided group [ROB], n = 20) and a manual arm-based technique (group MAN, n = 20). RESULTS: Application of the robotic technique resulted in significantly higher accuracy at entry point (group ROB median 1.5 mm [0.4-3.2 mm] vs manual arm-based group (MAN) 2.2 mm [0.2-5.2 mm], P  = .019) and at target point (group ROB 1.5 mm [0.4-2.8 mm] vs group MAN 2.8 mm [1.4-4.9 mm], P  = .001), without increasing incision to suture time (group ROB 30.0 min [20-45 min vs group MAN 32.5 min [range 20-60 min], P  = .09) and significantly shorter skin incision length (group ROB 16.3 mm [12.7-23.4 mm] vs group MAN 24.2 mm [18.0-37.0 mm], P  = .008). CONCLUSION: According to our data, the proposed technique of minimally invasive robot-guided brain biopsies can improve accuracy without increasing operating time while being equally safe and effective compared to a standard frameless arm-based manual biopsy technique.